(untitled) (Desenvolvimento em Questão, 2025)
The implementation of a suitable solid waste management policy is challenging, especially for communities in the middle of Amazonia, which do not have basic sanitation services, such as waste collection. Thus, this study aims to evaluate the fate of solid waste produced in riverine communities in the rural region, state of Amazonas, Brazil. Thus, a sample comprising 120 localities and 775 households was analyzed, based on census data collected in 2018 by the Demographic and Economic Monitoring System (SIMDE) of the Mamirauá Institute for Sustainable Development, within the Amanã Sustainable Development Reserve. The main destinations of the waste were the burning of 70% of the flammable waste, and the burial of 63% of the other waste generated. Due to the lack of adequate disposal options, riverine communities have developed their own methods for the final disposal of household waste. These findings underscore the urgent need to promote more appropriate and sustainable solid waste management practices in rural communities of the Amazon.